PENGARUH WORKING CAPITAL MANAGEMENT TERHADAP PROFITABILITAS PADA PERUSAHAAN DENGAN FIRM SIZE, OPERATING LEVERAGE, DAN CURRENT RATIO SEBAGAI VARIABEL KONTROL (Studi Pada Perusahaan Sektor Pertambangan di Bursa Efek Indonesia) - Ramadhan, Rian Rahmat; Hasan, Amir; Efni, Yulia (Jurnal Tepak Manajemen Bisnis, 2017)
This study aims to determine the effect of DSO, DIO, DPO and CCC against mining companies in Bursa Efek Indonesia. The population of this research is all mining companies in Bursa Efek Indonesia. Sampling method using purposive sampling method. The research sample of 28 mining companies. Methods of data collection using literature and documentaries. Data analysis techniques using multiple linear regression with the help of software Eviews 9. The results DSO, DIO DPO, and CCC have a significant effect on the profitability of the Company. DPO has a positive effect on the profitability of mining companies.